1994
DOI: 10.1093/rheumatology/33.7.644
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Permeability in Patients With Ankylosing Spondylitis and Their Healthy Relatives

Abstract: Patients with AS were previously found to have increased intestinal permeability using the 51Cr-EDTA resorption test. In order to discover whether this alteration has taken place prior to, or as a consequence of the disease, we studied the intestinal permeability to 51Cr-EDTA in 20 patients with AS, 65 of their healthy relatives, and 25 normal volunteers. We also considered the HLA B27 antigen, the serum immunoglobulin A levels, the disease activity, the existence of peripheral arthritis, the ESR, the CRP valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
6

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(54 citation statements)
references
References 0 publications
2
46
0
6
Order By: Relevance
“…The link between increased intestinal permeability and AS has been clearly established [50]. Using different markers of TJ permeability, two independent studies [51,52] found an increased intestinal permeability in both AS patients and their relatives. These changes precede the clinical manifestations of the disease, suggesting a pathogenic role of TJ dysfunction in AS.…”
Section: Ankylosing Spondylitismentioning
confidence: 99%
“…The link between increased intestinal permeability and AS has been clearly established [50]. Using different markers of TJ permeability, two independent studies [51,52] found an increased intestinal permeability in both AS patients and their relatives. These changes precede the clinical manifestations of the disease, suggesting a pathogenic role of TJ dysfunction in AS.…”
Section: Ankylosing Spondylitismentioning
confidence: 99%
“…The increased prevalence of AS in young adult males may result from a higher starch intake and consequent increase in Klebsiella growth in the gut. 2 The site at which the triggering infection occurs is unclear, but the presence of histological signs of inflammation 86 and increased gut permeability 79 in patients with AS suggests an overt or occult enteric infection.…”
Section: Environmental Triggersmentioning
confidence: 99%
“…It may be of greater significance that 21-60% of first-degree relatives of patients with non-NSAIDtreated AS had increased intestinal permeability (53,54). These findings parallel the increased intestinal permeability found in 10-54% of first-degree relatives of patients with Crohn's disease (49,55,56).…”
Section: Effect Of Treatment On Spondylarthropathic Ileitismentioning
confidence: 99%